KNOWLEDGE AS THE INTERVENING VARIABLE ON RELIGIOSITY VALUE OF ACCOUNTANT STUDENTS' SAVING INTEREST FOR ISLAMIC BANKING - Wahyuning Murniati; Evita Purnaningrum (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
The development of Islamic economics in banking practices in society develops innovatively. Various sharia banking products have become the people's choice in supporting their daily economic activities. The same thing also happened to students. The purpose of study is to analyze the religiosity effect of students' interest in saving for Islamic banking with knowledge as intervening variable. Multiple linear regression is an analytical technique used here, with hypothesis testing and path analysis to support its conclusions. The result of this study is that the level of religiosity significantly effects on students' interest in saving for Islamic banking with positive relationship. Likewise, knowledge is able mediate the relationship between the religiosity variable and students' interest in saving.